Collective Action Kelompok Sadar Wisata Desa Malaka Dalam Percepatan Pariwisata Guna Peningkatan Ekonomi Masyarakat - Amniatin Naqiah; Ilham Zitri; Amil (Indonesian Journal Publisher, 2023)
This research was conducted to find out how the collective action of tourism awareness groups (Pokdarwis) in accelerating tourism in order to increase the community's economy in Malacca Village, Pemenang District, North Lombok Regency. The role of Pokdarwis in accelerating tourism to build and develop the tourism sector is urgently needed because the tourism sector is currently a sector that plays an important role in people's income and is a source of the community's economy. This study uses a qualitative research method (qualitative research), namely by: observation to research sites, case studies where researchers carry out in-depth exploration of the events studied by researchers. The data sources used in this study are primary data sources obtained from direct observation at the research site and secondary data sources obtained from related institutions and sources processed by researchers. The results of this study indicate that the results of Pokdarwis' collective action in Malaka Village have been successful. This can be seen from the several actions taken by Pokdarwis with the community and also other parties, namely by carrying out namely: involving the community in managing tourist attractions, building and updating existing facilities in tourist attractions, increasing human resources (HR) through training at the North Lombok Tourism Office and building cooperation with the local government and the community, so that currently the economy of the people in Malacca Village is well fulfilled. Currently the tourism sector in Malacca Village has not involved the private sector in its management. However, the current obstacle is the support from the Malaka Village government which is still lacking in terms of facilitating the tourism sector such as: the availability of proper seats, inadequate trash cans, prayer rooms that look worn out and toilets that are not suitable for use, and lack of promotion in the media social media or through a special blog for tourist attractions in Malacca Village. If the facilities at tourist attractions are properly met, of course the public and tourists will feel comfortable enjoying their vacation because their needs have been properly met.